Modelling sound absorption properties for recycled polyethylene terephthalate-based material using Gaussian regression. Issue 2 (June 2021) - Iannace, Gino; Ciaburro, Giuseppe
Plastic is widely used all over the world and its production has been increasing continuously in recent years. But plastic presents significant problems about its end-of-life given its important environmental impact. These problems impose recycling policies which provide for the collection and recycling of plastic materials. In this work, the acoustic properties of a recycled polyethylene terephthalate-based material were analyzed. The material showed good sound-absorbing characteristics, especially at high frequencies. In addition, a numerical model based on the Gaussian regression was developed to simulate the sound absorption coefficient of the material. The model returned an R-Squared value of 0.97 demonstrating excellent performance.